Effects of recipient oocyte source, number of transferred embryos and season on somatic cell nuclear transfer efficiency in sheep. Issue 11 (17th September 2019) - Yuan, Yixin; Liu, Ruming; Zhang, Xiaosheng; Zhang, Jinlong; Zheng, Zi; Huang, Chengjun; Cao, Guifang; Liu, Haijun; Zhang, Xianfu
Abstract: To improve the efficiency of somatic cell nuclear transfer (SCNT) in sheep, we investigated the effects of recipient oocyte source, number of transferred embryos and season on the pregnancy and live lamb rates for sheep somatic cell nuclear transfer embryos. Follicle‐stimulating hormone (FSH)‐stimulated ovaries produced significantly more oocytes both in total and of suitable quality for maturation culture than those without FSH treatment (from slaughterhouse). However, their in vitro maturation rates were similar. Embryos were reconstructed using adult fibroblast cells into enucleated MII oocytes. The pregnancy and term rates were significantly higher in the FSH‐stimulated group than in the slaughterhouse one. Oocytes from FSH‐stimulated ovaries were enucleated as recipient cytoplasm for nuclear transfer in the following experiments. The transfer of 7–9 and 11–13 embryos produced significantly higher pregnancy rates than that of six embryos. However, the former groups exhibited similar live lamb rates. FSH‐stimulated ovaries produced significantly more oocytes in November and December (winter) than in May to July (summer), but the associated maturation rate did not increase. Pregnancy and term rates were significantly higher when transfer occurred in winter than in summer. In conclusion, FSH treatment produced significant benefit regarding the number and quality of collected oocytes and also for the pregnancy and live lamb rates for reconstructed embryos. However, the transfer of an appropriate number of embryos (7–13) and at an appropriate season (winter) increased pregnancy and term rates.